Density of Langerhans cells in the keratocystic odontogenic tumor - Meira,Thiago Martins (2010)
INTRODUCTION: Keratocystic odontogenic tumors (KOTs) are distinct odontogenic lesions commonly affecting the mandible bones. Langerhans cells (LCs) are specialized dendritic cells responsible for the presentation of antigens to T lymphocytes in mucosal and cutaneous surfaces. OBJECTIVE: This study analyzed the immunohistochemical expression of LCs in KOTs. MATERIALS AND METHODS: Fifteen cases of KOTs were studied using the anti-CD1a marker. Results: LCs were observed in all 15 cases analyzed. They were found to be concentrated in areas of cystic epithelial hyperplasia, mainly in those areas presenting higher concentration of inflammatory cells. Furthermore, a significant association between the number of LCs and areas of cystic epithelium presenting hyperplasia (Mann-Whitney test, p = 0.0223) was observed. The shape and location of these cells in KOTs epithelium were variable. CONCLUSION: The lower number of LCs observed on atrophic cystic epithelium of KOTs may be due to decreased epithelial immunosurveillance and this may result in locally aggressive invasiveness.